Optimization of Vaccine Virus Accumulation in the Development of Smallpox Drugs Based on Cell Cultures - A. V. Ovchinnikov; G. V. Borisevich; A. I. Terent’ev; Yu. I. Pashchenko; V. T. Krotkov; V. N. Marchenko; S. V. Borisevich; S. L. Kuznetsov (Проблемы особо опасных инфекций, 2019)
Objective. Optimization of vaccine virus cultivation in the suspended cell culture BHK-21 for infectious activity increment of virus-containing suspension as the base material for smallpox vaccine preparations. Materials and methods. We used suspended culture line of the cells BHK-21 of 72-hour age and nutrient medium of the MEM type in accordance with the guidelines on preparation in our studies. For challenging of the cells, vaccine virus (strain B-51) was used. The virus was adapted through three consequent passages on horion-allantois shell of developing chicken embryos of commercial dermovaccine series 449а at the premises of the Federal State Budgetary Institution “the 48th Central Research Institute” of the Ministry of Defense of the Russian Federation. Information on its genetic features is absent. Cultivation and precipitation of infected cells BHK-21 was carried out in bioreactor with priming volume of 1 liter at (36.5±0.5) °C and aeration with air mixture with varying content of CO2. Results and conclusions. Gas  massexchange intensity was enhanced alongside simultaneous maintaining of sparing hydrodynamic conditions for mixing suspended cell cultures in bioreactor. Two-fold increase (up to (4.48±0.63)·109 cell/l) in suspended BHK-21 cell culture concentration at the end of reproduction cycle was achieved. Concentration of the vaccine virus was 3–5 times raised, from (8.1±0.3) lg PFU (plaque forming unit)/ml up to the level of infectious activity – (8.8±0.3) lg PFU/ml. Specific multiplicity of cell infection in recalculation per a cell was 1–5 PFU/cell and by virus yield – 20–100 PFU/cell. Enhanced infectious activity of the virus in concentrated suspension of infected BHK-21 cells substantiates the perspectives of the proposed method for improvement of vaccine virus accumulation phase in the development of anti-smallpox preparations based on cell cultures.